Reproductive investment of the pen shell Pinna nobilis Linnaeus, 1758 in Cabrera National Park (Spain) - DEUDERO, S.; GRAU, A.; VÁZQUEZ-LUIS, M.; ÁLVAREZ, E.; ALOMAR, C.; HENDRIKS, I. E. (Mediterranean Marine Science, 2017)
The spawning period can be a period of particular vulnerability for a species. In hermaphroditic species like the long-lived pen shell Pinna nobilis different costs could be associated with female, male or hermaphrodite stages. Here we evaluate gonad development in a population with few anthropogenic pressures and describe the timing and succession of developmental stages, determine the ratio of the sexes and the condition of the animals. We assess resource mobilisation and associated costs through the relationship between stable isotopes and condition indexes with reproductive parameters and evaluate the role of the adductor muscle as storage organ used in gonad maturation. In our study area only one spawning season is observed, starting in May and peaking in June-July. The onset of spawning coincides with water temperatures of 20 °C. Condition indexes drop during the spawning period and recover afterwards to reach pre-spawning values in November. Stable isotope signals are negatively related to the gonadal condition index, while the CN ratio shows a positive correlation with the same index. Additionally, the muscle condition index sharply decreases after the start of the spawning season, which suggests that P. nobilis uses the reserves stored in the adductor muscle for reproduction as in other Pinnidae species. Reproductive indices and stable isotopes ratios indicate ‘capital breeding’ as reproductive strategy of the pen shell. Decreased muscle force could mean a higher vulnerability during the summer period, coinciding with the peak in recreational activities involving poaching and anchoring.